123 Polyclonal antibody preparations from avian origin did not reduce plasmatic haptoglobin concentrations but increased ruminal NH3-N in beef steers during transition from forage to high-grain diets. (28th November 2020) - da Silva, Gleise Medeiros; Podversich, Federico; Schulmeister, Tessa M; Santos, Erick Rodrigo Silva; Sanford, Carla; Siqueira, Michelle C B; Tarnonsky, Federico; DiLorenzo, Nicolas
Abstract: This study investigated the effects of feeding an avian-derived polyclonal antibody preparation (PAP; CAMAS, Inc.) against Streptococcus bovis, Fusobacterium necrophorum, and lipopolysaccharides (40, 35, and 25% of the preparation, respectively) on plasmatic haptoglobin, ruminal short chain fatty acids (SCFA), and ammonia-N (NH3 -N) concentrations of beef steers during a 21-d step-up adaptation to a high-grain diet. Eight ruminally cannulated Angus crossbred beef steers (658 ± 79 kg BW) were randomly assigned to treatments in a crossover design to be transitioned from a diet containing bermudagrass hay [Cynodon dactylon (L.) Pers.] plus 0.45 kg/d of molasses with 0 (CON) or 3 g/d of PAP (PAP) to a high-grain diet. Transition consisted of three 7-d steps of increased inclusion of cracked corn (35, 60, and 80% diet DM for STEP1, STEP2, and STEP3, respectively). On each transition d and 7 d after STEP3 (STEP3-7d), ruminal fluid samples were obtained every 3 h for 24 h. Blood samples were collected on d 0, 1, and 3 relative to each transition for haptoglobin determinations. Haptoglobin plasmatic concentrations increased (P = 0.03) on d 2 and 3 vs. d 1 during STEP2 and on STEP3 compared to STEP1 and STEP2 (P = 0.01). Steers receiving PAP had greater (P < 0.01) ruminal NH3 -N concentration in STEP1; however, there were no effects of treatment on SCFA (P > 0.10). Total SCFA concentrations were affected by the step-up diets (P < 0.01); propionate concentration (Pro) was greater in STEP2 through STEP3-7d vs. STEP1 (P < 0.01), whereas acetate concentration (Ac) and Ac:Pro linearly decreased from STEP1 to STEP3-7d (P < 0.01). Feeding 3 g/d of polyclonal antibody preparations against Streptococcus bovis, Fusobacterium necrophorum, and lipopolysaccharides in a 21-d step-up adaptation to high-grain diets did not affect plasmatic haptoglobin or ruminal SCFA concentrations; however, it increased ruminal NH3 -3 concentrations.